Has Inventory Investment Been Liquidity-Constrained? : Evidence From U.S. Panel Data - Kim, Yungsan (IMF Working Papers; Working Paper, 2001)
Based on an analysis of high-frequency panel data for U.S. firms, this paper finds that inventory investment has been liquidity-constrained in most periods during 1975-97, but less so, or not at all, during recessions. This result can be justified on the grounds that inventory fluctuations are largely attributable to unexpected sales shocks, and that firms increase liquid assets before recessions. Moreover, this results holds irrespective of whether the firm has a bond rating, contrary to the finding of Kashyap, Lamont, and Stein (1994) that inventory investment is liquidity-constrained during recessions only for firms without bond ratings.